Seroprevalence and Risk Factors for Cysticercosis in Mexican Americans in Starr County, Texas - Megan M. Duffey; Elise M. O’Connell; Morgan Jibowu; Fanny E. Moron; Lauren M. Leining; Nina L. Tang; Craig L. Hanis; Eric L. Brown; Sarah M. Gunter (Pathogens)
Cysticercosis is a parasitic infection and neglected tropical disease caused by Taenia solium, or the pork tapeworm. Cysticercosis with central nervous system involvement, or neurocysticercosis, is a leading cause of chronic headaches and epilepsy in endemic regions, including Latin America and Asia. In the United States, the epidemiology of cysticercosis has not been well described. We conducted a cross-section serosurvey of Mexican-American adults residing along the Texas–Mexico border (Starr County, Texas) and identified an overall seroprevalence of 7.4% (45/605) for cysticercosis. Brain imaging studies conducted on seropositive study participants identified lesions consistent with calcified neurocysticercosis in 2 of the 45 seropositive individuals. Female sex (p = 0.021), employment in healthcare, caregiving, or social service (p = 0.002), and indoor occupation (p < 0.001) were found to be significantly associated with seropositivity. Further study is needed to evaluate the burden of neurocysticercosis and local transmission risk in this community.